Potential for methane digesters on U.S. dairy farms - Brooks, Dana L. (Kansas State University, 2013)
Methane digesters are a potential investment for a dairy farm. A digester can lower greenhouse gas emissions, manage manure waste, generate energy, provide fertilizer and recycle bedding. The AgSTAR project of the Environment Protection Agency describes anaerobic digesters as a solution to a problem dairy farmers have always had to solve but that has become more acute with the innovation of larger scale, confined animal feeding operations developed in response to the growing food demands of the world’s larger and more prosperous middle class population – what to do with cow manure. Digesters take cow manure and convert it into energy while also eliminating manure odor. Energy is the primary economic benefit of a digester. A dairy farmer can use the electricity or gas generated from the digester to fuel the energy needs of the farm. Selling gas or electricity on the market is a revenue source that largely determines the level of profit from investing in a digester. This thesis will explore the four economic factors required to make anaerobic digesters a viable economic investment for a 1,500 head cow herd in the United States. It is imperative that farmers are able to obtain a return on the investment as soon as possible as many do not have the capital to invest in a nearly $1 million project. Congress may need to provide additional incentives for farmers and utility companies to take waste and process to energy. The future for methane digesters looks profitable when energy and carbon markets are available and allowed to trade competitively. The federal government may consider focusing on incentives for the utility companies’ infrastructure to make purchases of renewable energy from a digester more economically attractive and efficient. Today, an obstacle for increasing the number of digesters in the United States is the cost associated with moving the energy from the digester and into the national natural gas to grid. Natural gas companies may need to be compensated for that expense plus the potential difficulties of dealing with multiple suppliers or digester owners. Electricity companies have a grid in place to power rural and urban communities. They have spent billions of dollars and decades to establish efficient routing of power to residents and businesses. Manure digesters are mostly located in rural areas that would also require an investment in infrastructure to move the energy from the digester to the power grid. Mandating net-metering would require energy companies to purchase renewable energy, but consumers may see an increase in their cost. Therefore, the answer to increasing the number of manure digesters in the United States may be to direct the incentives to utility companies to invest in expanding infrastructure rather than increasing digester owner subsidies. Although, the REAP grants are helpful for assisting farmers with startup installation costs, there may not be a need to increase that subsidy in the next farm bill if an energy bill includes incentives for energy companies to purchase renewable energy from digesters.
Keywords: Methane digester; Dairy economics; Policy; Energy; Manure; Carbon Credits; Agriculture, General (0473); Economics, Agricultural (0503); Political Science (0615)